Struktur Dewan Direksi dan Insider Trading - Herdiani, Aulia; Wu, Ruei-Shian (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
Studies on how to mitigate insider trading have been extensively conducted, but various monitoring schemes have produced mixed results. This study attempts to examine the impact of internal monitoring mechanisms through the structure of board directors on insider tendencies. This study examines nine characteristics of the board of directors’ structure on abnormal returns from insider trading as measured using the Carhart (1997) four-factor model estimated more than 180 calendar days after the transaction dates. The results indicate that the influence of the structure of board directors varies on insider selling and purchasing. The independent directors on board structure monitoring mechanism are more effective in mitigating insider selling, but not for insider purchasing.